2019
DOI: 10.1177/2055668319854340
|View full text |Cite
|
Sign up to set email alerts
|

Garments for functional electrical stimulation: Design and proofs of concept

Abstract: Introduction Repeated use of functional electrical stimulation can promote functional recovery in individuals with neurological paralysis. We designed garments able to deliver functional electrical stimulation. Methods Shirts and pants containing electrodes knitted with a conductive yarn were produced. Electrodes were moistened with water before use. Stimulation intensity at four thresholds levels (sensory, movement, full range of motion, and maximal), stimulation comfort, and electrical properties of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 68 publications
1
56
0
4
Order By: Relevance
“…In their study, they found a wet textile-based electrode was able to produce movement, similar to a hydrogel, while applying stimulation with a dry textile-base electrode produced pain even at low stimulation currents. Similar observations were reported by [65] when using their garments for FES delivery.…”
Section: Textile-based Fessupporting
confidence: 86%
See 2 more Smart Citations
“…In their study, they found a wet textile-based electrode was able to produce movement, similar to a hydrogel, while applying stimulation with a dry textile-base electrode produced pain even at low stimulation currents. Similar observations were reported by [65] when using their garments for FES delivery.…”
Section: Textile-based Fessupporting
confidence: 86%
“…More importantly, textile-based garments can also be integrated into regular clothing which has the potential to simplify the delivery of FES and, consequently its use. This is further supported by the fact that garments can be mass-produced [65]. Examples of textile-based electrodes include the Smart Electrode and the Smartex [66].…”
Section: Textile-based Fesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, despite the potential of wearable FES garments, the stimulation comfort of textile electrodes remains of concern [3]. For example, researchers [3,4] found that textile electrodes produced by knitting technologies required continued moistening to exhibit comparable stimulation performance to traditional electrodes. There has also been an increased focus on the development of dry-contact textile electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Як правило, електростимулятори розташовують на ділянках переднього та заднього дельтовидних м'язів, трицепса і біцепса, нижче колін, сідничного м'яза, прямого м'яза живота, а також в області поперекового відділу хребта. Розробники пропонують виготовляти такі стимулятору розміром з iPad [6].…”
unclassified